Ferroic hysteresis modeling - S. Srinoi (2018)
Ferroic hysteresis modeling is an approach applicable to study lagging relationship between ferroic properties and external-dynamic-perturbation behaviors. The understanding to the lagging hysteresis behaviors, such as hysteresis area, coercive field, or remnant magnetization/polarization, is essential to the material-industry development. In this review, fundamental analysis as a microscopic study, including spin models, mean-field method and Monte Carlo simulation, and data processing analysis as a linking bridge between macroscopic analysis and the experiment results, such as the artificial neutral network (ANN) and Fourier analysis, were elaborated on how they can be used to model the dynamic ferroic hysteresis. Then, ferroic behaviors were explained on how they depend on the external perturbations, such as the field parameters and temperature. The responses of ferroic behaviors on these factors, in both qualitatively and quantitatively, were also discussed in details. © 2011 Copyright Taylor and Francis Group, LLC.